Cyclops: Designing an Eye-Controlled Instrument for Accessibility and Flexible Use - Payne, William; Paradiso, Ann; Kane, Shaun K. (NIME'20, 2020)
The Cyclops is an eye-gaze-controlled instrument designed for live performance and improvisation. It is primarily motivated by a need for expressive musical instruments that are more easily accessible to people who rely on eye trackers for computer access, such as those with amyotrophic lateral sclerosis (ALS). At its current implementation, the Cyclops contains a synthesizer and sequencer, and provides the ability to easily create and automate musical parameters and effects through recording eye-gaze gestures on a two-dimensional canvas. In this paper, we frame our prototype in the context of previous eye-controlled instruments, and we discuss how we designed the Cyclops to make gaze-controlled music making as fun, accessible, and seamless as possible despite notable interaction challenges like latency, inaccuracy, and “Midas Touch.”